2014
DOI: 10.1007/s11356-014-3958-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sample pretreatment on the fractionation of arsenic in anoxic soils

Abstract: Using by sequential extraction procedures to obtain the chemical forms of arsenic in soils can provide useful information for the assessment of arsenic mobility and bioavailability in soils. However, sample pretreatments before the extraction probably have some effects on the fractionation of arsenic in soils. Impact of sample pretreatments (freeze-drying, oven-drying, air-drying, and the fresh soil) on the fractionation of arsenic in anoxic soils was investigated in this study. The results show that there are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 46 publications
1
23
0
Order By: Relevance
“…3), indicating that high As load and low oxygen conditions are likely to prolong the formation of F6 in soils. The association of As and sulfides such as arsenopyrite and orpiment may be responsible for the longer time required for the formation of F6 in the low oxygen condition than in the aerobic condition (Kim et al, 2000;Huang et al, 2015). The phenomenon of quickly reaching equilibrium of F6 formation was also reported by Tang et al (2007), who noted that the proportion of F6 reached a steady state within one week in some Chinese soils, but it is distinct from another study showing that the increase of F6 in some Fe-rich soils lasted for N 12 months (Juhasz et al, 2008).…”
Section: Influences Of As Load and Redox Condition On As Fractionsmentioning
confidence: 99%
“…3), indicating that high As load and low oxygen conditions are likely to prolong the formation of F6 in soils. The association of As and sulfides such as arsenopyrite and orpiment may be responsible for the longer time required for the formation of F6 in the low oxygen condition than in the aerobic condition (Kim et al, 2000;Huang et al, 2015). The phenomenon of quickly reaching equilibrium of F6 formation was also reported by Tang et al (2007), who noted that the proportion of F6 reached a steady state within one week in some Chinese soils, but it is distinct from another study showing that the increase of F6 in some Fe-rich soils lasted for N 12 months (Juhasz et al, 2008).…”
Section: Influences Of As Load and Redox Condition On As Fractionsmentioning
confidence: 99%
“…Since some dissolved As in sediment solution remained within the wet sediment samples, both the dissolved and water-soluble As were removed by shaking the sample at 180 rpm with 25 mL deionized water for 5 min three times. After that, the samples were freeze-dried for subsequent experiments to avoid redistribution among As fractions and speciation (Huang et al 2015). Five-step sequential extraction was carried out according to the method described by Wenzel et al (2001).…”
Section: Sequential Extraction Of Adsorbed Asmentioning
confidence: 99%
“…Irrigation of paddy fields with As-rich groundwater and mining activities have caused serious contamination of paddy soils (Huang et al, 2006;Wang et al, 2015;Xue et al, 2016). Liao et al (2005) reported that As concentrations in rice grain grown in As-contaminated soils reached 7.5 mg/kg.…”
Section: Introductionmentioning
confidence: 99%